1986
DOI: 10.1177/030098588602300601
|View full text |Cite
|
Sign up to set email alerts
|

Cytologie Differentiation of Benign from Malignant Canine Mammary Tumors

Abstract: Abstract. Cytologic and histologic examination of 91 canine mammary masses was performed by two cytologists and two histopathologists. Ten important cytologic criteria of malignancy for canine mammary tumors were identified. A cytologic grading system for differentiation of benign from malignant mammary tumors was proposed using these criteria. With this system, approximately one fourth of the malignant mammary tumors were given a concordant cytologic diagnosis. Approximately one-half of the benign masses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
74
4
15

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 17 publications
(4 reference statements)
7
74
4
15
Order By: Relevance
“…Estes podem ser justificados, pois tumores de origem mesenquimal, sólidos e complexos e mistos, possuem baixa capacidade esfoliativa, e processos císticos podem conter poucas células, inviabilizando a análise citopatológica adequada (Allen, 1986).…”
Section: Resultsunclassified
“…Estes podem ser justificados, pois tumores de origem mesenquimal, sólidos e complexos e mistos, possuem baixa capacidade esfoliativa, e processos císticos podem conter poucas células, inviabilizando a análise citopatológica adequada (Allen, 1986).…”
Section: Resultsunclassified
“…Grossly they vary from well-circumscribed nodules with stationary growth to large and sometimes ulcerated nodules, which grow rapidly and become fixed to adjacent tissues. The initial diagnosis of CMTs is based on clinical signs and symptoms and while fine-needle aspiration may be useful (Hellmen and Lindgren, 1989), histology is necessary for an accurate diagnosis (Allen et al, 1986). Malignant canine mammary tumours are more frequent than benign ones (Brodey et al, 1983;Shekhar et al, 2001;Reddy et al, 2009).…”
mentioning
confidence: 99%
“…In the case diagnosed in this study, the radiological examination also revealed lung metastases, as frequently cited by other authors. Although in this study we diagnosed one case of malignant mammary neoplasia, according to data from the literature, mammary neoplasia remains one of the most common clinical problems of adult female dogs, representing 50-70% of the diagnosed neoplasms in dogs (Allen et al, 1986;Murakami et al, 2000).…”
Section: Resultsmentioning
confidence: 99%